Ihsan in charity as the basis for the formation of human resources - Rakhmad Agung Hidayatullah; Hamid Fahmy Zarkasyi; Fuad Mas’ud; Khoirul Umam; Usmanul Khakim (al-Afkar, Journal For Islamic Studies, 2025)
Human beings, basically, have a tendency to do things that like virtuous values, but in the process of their development, human beings are greatly influenced by their environment, Allah Himself has outlined that in human beings there is a tendency in two directions, namely actions that deviate from the rules and those that obey the rules. Man also has the tendencies mentioned above, he also has the freedom to choose between two paths, namely the right and the wrong. Therefore, humans can be wrong in choosing and judging a good deed, due to the lack of knowledge, the environment. Considering the possibility of human error or mistake in choosing and judging good deeds, Allah teaches people about goodness by mentioning and informing through the Qur'an which was revealed to the Prophet Muhammad (saw) in several terms. Among these terms are the word ihsan and term Prophet Muhammad (saw) in several terms. Among these terms are the word ihsan and other terms. To be more in-depth about the Qur'an's insight into ihsan or goodness, this paper will discuss the Qur'an's insight into ihsan or goodness.